2002
DOI: 10.21273/jashs.127.3.435
|View full text |Cite
|
Sign up to set email alerts
|

Methyl Jasmonate Enhances Anthocyanin Accumulation and Modifies Production of Phenolics and Pigments in `Fuji' Apples

Abstract: Effects of artificial ultraviolet-visible light and methyl jasmonate (MJ) treatment on `Fuji' apple [Malus sylvestris (L.) Mill. var. domestica (Borkh.) Mansf.] fruit peel anthocyanin, phenolic, carotenoid, and chlorophyll production were examined using tristimulus color analysis and reverse-phase high performance liquid chromatography. Anthocyanin synthesis was enhanced by light and MJ treatment. Chlorogenic acid and most cyanidin, quercetin, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
80
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(95 citation statements)
references
References 48 publications
13
80
0
2
Order By: Relevance
“…Similar to the findings of Kondo et al [15] and Rudell et al, [25] the MeJA treatments in the present study distinctively increased the anthocyanin contents in both experimental years. A clear linear relationship was observed between the treatment doses and the anthocyanin contents.…”
Section: Resultssupporting
confidence: 93%
“…Similar to the findings of Kondo et al [15] and Rudell et al, [25] the MeJA treatments in the present study distinctively increased the anthocyanin contents in both experimental years. A clear linear relationship was observed between the treatment doses and the anthocyanin contents.…”
Section: Resultssupporting
confidence: 93%
“…The maximum values were observed 72 h after treatment and then a slight decline followed over time. Rudell et al (2002) showed no clear correlation between chlorophyll a and xanthophylls content and MeJA treatment in an experiment with apples, but chlorophyll b and b-carotene synthesis increased linearly with MeJA concentration. Czerpak et al (2006) in their study with JAtreated Chlorella vulgaris showed, that a higher concentration range (10 -5 -10 -4 M) resulted in a decrease in cell number and a reduction of major photosynthetic pigments, but in contrast, this phytohormone applied at 10 -8 -10 -6 M induced an increase in the cell number and photosynthetic pigments.…”
Section: Discussionmentioning
confidence: 81%
“…(Rudell & Mattheis, 2002), and grapes -V. vinifera L. cvs. Isabelle (Mihai, Mitoi, Brezeanu, & Cogalniceanu, 2010).…”
Section: Resultsmentioning
confidence: 99%